PENGARUH ISLAM PADA TAMBO DALAM NARASI SEJARAH ASAL MUASAL DAN TRANSFORMASI SOSIAL MASYARAKAT MINANGKABAU - Pratama, Fikri Surya; Yola, Nilma; Husni, Nurul Izzati (Pusat Riset Manuskrip, Literatur, dan Tradisi Lisan, 2023)
As a literary work of the Minangkabau people, Tambo is said to be historical literature. In content, this tambo does not explain the existence of King Adityawarman as part of Minangkabau history, and only highlights figures who are Muslim. This research aims to analyse the extent of Islamic influence in the tambo manuscript, with the primary source of the manuscript